Nursing shift handover methods and their impact on patient safety - N. K., Kavitha; Abi Rami, M.; Vanaja, P.; A. K., Manjula; Jaspher M., Justin; Prabu D., Israel Jeba; K., Lakshimi; Katiyar, Jyoti; Umar, Mohammed; Prabha, N. (International Journal of Research in Medical Sciences, 2026)
Nursing shift handover is a critical patient safety practice that underpins continuity of care, clinical accountability, and risk mitigation in complex healthcare environments. Communication failures during handover remain a leading contributor to preventable adverse events, including medication errors, patient falls, pressure injuries, and delayed recognition of clinical deterioration. This systematic review synthesises current evidence on nursing shift handover methods and their impact on patient safety outcomes in inpatient settings. A comprehensive systematic search of major databases, including PubMed, Scopus, CINAHL, Embase, and the Cochrane Library, was conducted following PRISMA 2020 guidelines. Studies published between 2008 and 2025 evaluating bedside nursing handover, structured communication frameworks such as SBAR/ISBAR, integrated verbal–written systems, and electronic handover tools were included. Quantitative, qualitative, and mixed-methods studies were synthesised using a narrative approach due to methodological heterogeneity. Findings indicate that structured and standardised handover interventions are consistently associated with improvements in communication quality, handover completeness, and shared situational awareness. Bedside nursing handover demonstrates additional benefits through real-time patient verification and engagement, contributing to reductions in falls, medication administration errors, and pressure injuries in several settings. Electronic and integrated handover systems enhance information continuity but require robust governance to prevent data inaccuracy and over-reliance on documentation. Overall, this review underscores nursing shift handover as a high-impact, nurse-led safety intervention. Embedding structured, patient-centred, and context-sensitive handover models within organisational safety frameworks has the potential to substantially strengthen patient safety and quality of care.